2020
DOI: 10.1038/s41598-019-57244-7
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for the design of an effective air quality monitoring network in port areas

Abstract: The assessment of the impact of ship emissions is generally realised by a network of receptors at ground level inside the port area or in the nearby urban canopy. Another possibility is the use of dispersion models capable of providing maps of concentrations to the ground taking into account ship emissions and weather conditions. In this work traffic data of passengers ships in the port of Naples were used to estimate pollutant emissions starting from EMEP/EEA (European Environment Agency/European Monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 18 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…This proposed population-based representation evaluation method is different from existing methods that rely on spatial concentrations [ 19 , 21 , 56 ]. Based on our results, there is no apparent correlation between the size of the represented area and the actually represented population among the FSMs for any of the selected pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…This proposed population-based representation evaluation method is different from existing methods that rely on spatial concentrations [ 19 , 21 , 56 ]. Based on our results, there is no apparent correlation between the size of the represented area and the actually represented population among the FSMs for any of the selected pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…By applying the ADMS model in Bari, estimated impacts, considering both ship traffic and internal logistics activities (road vehicles and cranes), to specific receptor sites at different distances from the harbour, were highest for NO X (up to 40%) and PM 2.5 (up to 12%), compared to negligible contributions for CO and SO 2 (solely due to ships and markedly decreasing just outside the port area). Vertical profiles of SO 2 for some categories of vessels (cruise, ferries, and fast vessels) in Naples [99] revealed that, although cruise ships had the maximum absolute emissions, contributions at different heights of fast vessels were the highest. This study indicated that the best position of receptor points should not be at ground level inside the harbour area but between 20 and 50 m, corresponding to the maximum emissions for fast vessels and large ferries, respectively.…”
Section: Shipping Contribution To Concentration Of Atmospheric Pollutantsmentioning
confidence: 97%
“…As for CALMET, it functions as a meteorological model which handles on wind and temperature data (Scire et al, 2000) or in some cases, Weather Research and Forecasting (WRF) output file can be used as a reference for meteorological field (Mocerino, Murena, Quaranta, & Toscano, 2020). Another data involve in CALMET are surface characteristics, dispersion properties and mixing height.…”
Section: Calpuffmentioning
confidence: 99%
“…For another scope of research on air quality, this model is used for air quality monitoring. As stated in research by (Mocerino et al, 2020), CALPUFF model is applied on air quality monitoring of port area. Hence, the data needed are traffic data of ship passenger (used to estimate pollutants (SO2 and NO2 emission) and meteorological data.…”
Section: Calpuffmentioning
confidence: 99%